Relationship Between Internal Branding Practices, Brand Commitment and Employees' Brand Citizenship Behavior - Hasnizam, Shaari (2012)
Despite the growing popularity of the concept of internal branding in aligning employees’ brand behavior, little is known on how internal branding practices affect employees’ behavior toward the organization’s brand. The dearth of research in this field also limits the understanding of what is the appropriate employees’ behavior that could enhance their organization’s brand performance. Therefore, this study attempts to link the relationship of internal brand practices (namely brand knowledge, brand leadership and brand rewards) on employees’ brand citizenship behavior . Built based on Stimulus-Organism-Response Model, this study also attempts to test the mediation role of employees’ brand commitment on the initial relationship. 288 employees from twelve hotels in northern region of Malaysia in Perlis, Kedah and Penang consisted of three to five star rating participated in this study. Two parts of regression analyses were conducted. The first part dealt with general model specifically to answer the main hypotheses while the second part specifically conducted to answer subhypotheses of relationship between dimensions of each variable. The findings revealed that brand knowledge, brand leadership and brand rewards have a significant positive relationship with brand citizenship behavior as well as brand commitment. However, brand commitment only partially mediates the relationship between brand knowledge and brand leadership on brand citizenship behavior and fully mediate the relationship between brand rewards on brand citizenship behavior. The test of subhypotheses revealed that brand meaning, responsibility to deliver brand promise, transformational brand leadership and brand rewards have a significant positive relationship with helping behavior and self-brand-development. Sportsmanship is influenced by transactional and transformational brand leadership and brand rewards while brand endorsement is influenced by transactional brand leadership and brand rewards. Brand compliance partially mediates the relationship between brand rewards on sportsmanship while brand engagement partially mediates the relationship of (1) transformational brand leadership on helping behavior and (2) brand meaning and transformational brand leadership on self-brand-development.